Comparative Growth Rate of F1 and F2 Generations of Eucalyptus Hybrids Fri-4 and Fri-5 at Age 4 Years - Arya, R. S.; Sharma, V. K. (Indian Forester, 1990)
The paper summarizes the data on height, DBH and standing tree voulme of second generation hybrids (F1) of FRI-4 (E. tereticornis X E. camaldulensis) and FR-5 (E tereticornis X E. camaldulensis) along with their parents at age 4 years in a field trial laid out at New Forest, Debra Dun. The F2’s were compared with F1’s(FRI-4 and PRI-S)in respect of the height. DBH and volume for the data recorded at the corresponding age under the same site conditions. In general, overall performance of F2 shows that the heterosis has decreased in F2. However few recombinants in certain families have shown exceptionally good growth giving ample scope for further selection for raising F3.